Respuestas
Respuesta dada por:
0
Pendiente ( m)
m =![\frac{y1 - y2}{x1 -x2} \frac{y1 - y2}{x1 -x2}](https://tex.z-dn.net/?f=+%5Cfrac%7By1+-+y2%7D%7Bx1+-x2%7D+)
m =![\frac{5/4- (-21/4)}{7/2 - 5} \frac{5/4- (-21/4)}{7/2 - 5}](https://tex.z-dn.net/?f=+%5Cfrac%7B5%2F4-+%28-21%2F4%29%7D%7B7%2F2+-+5%7D+)
m =![\frac{26/4}{-3/2} \frac{26/4}{-3/2}](https://tex.z-dn.net/?f=+%5Cfrac%7B26%2F4%7D%7B-3%2F2%7D+)
m=
m =
m =
m =
m=
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años